Flaxseed mucilage as an eco-friendly inhibitor for ASTM A335 P11 steel in HCl - Angelats-Silva, Luis Manuel (2018)
The high efficiency of corrosion inhibition of synthetic organic inhibitors in the industries of chemical cleaning, acid etching, acidification of oil wells and acid desalination is well recognized. However, most of these inhibitors are toxic to the environment and human health. This has forced to look for more secure corrosion inhibitors called "green corrosion inhibitors" due to its non-toxicity, biodegradability and low cost. In recent years, the use of natural polysaccharides as an environmentally safe corrosion inhibitor has received special attention. For this reason, the present study, evaluates the mucilage of Linum usitatissimum, which contains a high content of polysaccharides, as a corrosion inhibitor of ASTM A335 grade P11 steel in HCl -1.0 M.